Prior Anticoagulation and Risk of Hemorrhagic Transformation in Acute Stroke: A Post Hoc Analysis of the PRODAST Study - Gerrit M. Grosse; Anika Hüsing; Andreas Stang; Nils Kuklik; Marcus Brinkmann; Martin Grond; Jens D. Rollnik; Lars Marquardt; Andrea Kraft; Eckhard Schlemm; Carsten Eggers; Christoph C. Eschenfelder; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Oral anticoagulation is highly effective in preventing ischemic events in patients with atrial fibrillation. Still, a considerable number of patients have an acute ischemic stroke or transient ischemic attack despite anticoagulation. In this study, we investigated the association of prior antithrombotic regimens with stroke severity, volume, and hemorrhagic transformation. Methods and Results This is a post hoc analysis of the prospective, multicenter, observational PRODAST (Prospective Record of the Use of Dabigatran in Patients With Acute Stroke or TIA) study, which was conducted in 86 stroke units in Germany between July 2015 and November 2020. In 9030 patients with atrial fibrillation who had an acute ischemic stroke or transient ischemic attack within 7 days before enrollment, we analyzed the association of anticoagulants in comparison to lack of prevalent antithrombotic treatment with clinical stroke severity, infarct size, and risk for hemorrhagic transformation. A total of 4479 patients had prior anticoagulation at the time of index event. After adjustment for confounders (arterial hypertension, diabetes, heart failure, age, and sex), patients with prior anticoagulation had less severe strokes (−2.5 National Institutes of Health Stroke Scale points [95% CI, −2.8 to −2.2]), smaller infarct sizes (−23 mL [95% CI, −44 mL to −2 mL], n=4041), and reduced odds for hemorrhagic transformation (5% versus 10%; odds ratio, 0.48 [95% CI, 0.40–0.57]) compared with patients without antithrombotic treatment. These findings were confirmed using sensitivity analyses accounting for thrombolysis and mechanical thrombectomy, as well as timing of brain imaging. Antiplatelet therapy had hardly any association with the end points compared with no antithrombotic pretreatment. Conclusions Prior anticoagulation was not only associated with less severe stroke and smaller infarct size but also with a reduced risk of hemorrhagic transformation compared with no antithrombotic pretreatment. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT02507856.